Energy Minimization of New Robotic-Type Above-Knee Prosthesis for Higher Battery Lifetime - Mucahit Ege; Serdar Kucuk (Applied Sciences, 2023)
In this paper, an optimization problem for the energy minimization of a new robotic-type three-axes above-knee prosthesis is carried out based on the actuator power consumption. The optimization problem aims to find the optimal link masses with which to minimize the electrical energy drawn from the battery of the new prosthesis, subject to the kinematic and dynamic constraints. Particle swarm optimization (PSO) is used as the optimization algorithm. A discrete-time PID controller is used to represent the saved energy by means of mass optimization. Optimization illustrated that energy consumption in the batteries can be reduced 51% and provides 1.89 h of additional battery lifetime, according to the literature, by optimizing prosthetic link masses while providing acceptable prosthesis stiffness.